Unraveling the role of ChREBP in lung adenocarcinoma: Expression, regulatory networks, and potential functional impact - Athisake Ruangpracha; Chanachai Sae-Lee; Pitaksin Chitta; Harald Grove; Pranisa Jamjuntra; Warisa Amornrit; Prapat Suriyaphol; Chanitra Thuwajit; Naravat Poungvarin (PLoS ONE, 2026)
Carbohydrate Response Element Binding Protein (ChREBP) is a transcription factor known to regulate glucose metabolism and other metabolic processes in various tissues, but its role in lung adenocarcinoma (LUAD) remains poorly understood. In this study, we investigated ChREBP expression and its role in regulating gene expression in LUAD cell lines. Using RT-qPCR, we assessed the expression of ChREBP-α and ChREBP-β isoforms in NCI-H1975, NCI-H1650, and NCI-H2228 LUAD cell lines. The NCI-H1975 cells exhibited the highest levels of both ChREBP isoforms, with a particularly pronounced expression of ChREBP-β. To explore the regulatory role of ChREBP, we generated NCI-H1975 cells with inducible expression of a dominant-negative mutant of human ChREBP (dnChREBP). Overexpression of dnChREBP led to a significant reduction in colony formation and impaired cell migration. Transcriptome analysis revealed 57 upregulated genes and 593 downregulated genes in dnChREBP-expressing cells compared to control cells. Functional annotation and gene set enrichment analysis revealed that the enriched genes were associated with cancer-related processes, including cell proliferation and epithelial-to-mesenchymal transition (EMT). Gene network analysis highlighted 17 downregulated hub genes, with 8 of these genes being associated with EMT. Interestingly, ChREBP and its transcriptionally regulated genes, including 4 top downregulated genes, 5 top upregulated genes, and 5 hub genes identified in NCI-H1975 cells overexpressing dnChREBP, showed significant prognostic value, as their expression levels correlated with overall survival in LUAD patients. Our findings suggest that ChREBP regulates distinct transcriptional programs in LUAD cells and ChREBP and its regulatory network may play a potential role in LUAD progression and patient outcomes.